2014
DOI: 10.1111/bph.12749
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of the mTOR‐signalling pathway in cancer: benefits and limitations

Abstract: The mammalian target of rapamycin (mTOR) plays an important role in the regulation of protein translation, cell growth and metabolism. The mTOR protein forms two distinct multi-subunit complexes: mTORC1 and mTORC2. The mTORC1 complex is activated by diverse stimuli, such as growth factors, nutrients, energy and stress signals; and essential signalling pathways, such as PI3K and MAPK, in order to control cell growth, proliferation and survival. mTORC1 also activates S6K1 and 4EBP1, which are involved in mRNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 133 publications
(203 reference statements)
2
97
0
Order By: Relevance
“…Naturally, targeting mTOR signalling pathway is a therapeutically attractive option for the purpose of sequestering eIF4E because 4EBPs are direct substrates of mTOR kinase (Ref. 130).…”
Section: Rapamycin and Rapaloguesmentioning
confidence: 99%
“…Naturally, targeting mTOR signalling pathway is a therapeutically attractive option for the purpose of sequestering eIF4E because 4EBPs are direct substrates of mTOR kinase (Ref. 130).…”
Section: Rapamycin and Rapaloguesmentioning
confidence: 99%
“…In this age-associated sarcopenia, it has been demonstrated that mTORC1 signaling is negatively controlled in those atrophied skeletal muscle cells [36,37]. As described, the reduction of glucose or amino acids can inactivate mTORC1 followed by decreased protein translation in skeletal muscle [30,31]. Because the small interference RNA-mediated suppression of endogenous sortilin inhibited C2C12 differentiation [7], it is indeed possible to speculate that the mTORC1-dependent sortilin regulation may contribute to the loss of skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 90%
“…Two major downstream targets for mTORC1 are also well defined, p70 S6 kinase (S6K1) and 4E-BP1. Phosphorylation of S6K1 at Thr389 by mTORC1 is a trigger for its activation [29], and the activated S6K1 phosphorylate S6 ribosomal protein, subsequently enhances the translation of mRNAs that have 5′ terminal oligopolypyrimidine [30]. On the other hand, 4E-BP1 normally binds to eukaryotic translation initiation factor 4E (eIF4E) and inhibits eIF4E-dependent protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activation of mTORC1 inhibits autophagy via phosphorylation of autophagy-related protein 13 and ULK1/2 (44). Rapamycin, a specific mTOR inhibitor, has been developed as an effective drug for the treatment of PJS and its associated tumors (22,45).…”
Section: Discussionmentioning
confidence: 99%